[RETRACTED ARTICLE] Long non-coding RNA HOTAIR promotes UVB-induced apoptosis and inflammatory injury by up-regulation of PKR in keratinocytes - Liu,Guo (2018)
Excessive exposure to ultraviolet (UV) rays can cause damage of the skin and may induce cancer, immunosuppression, photoaging, and inflammation. The long non-coding RNA (lncRNA) HOX antisense intergenic RNA (HOTAIR) is involved in multiple human biological processes. However, its role in UVB-induced keratinocyte injury is unclear. This study was performed to investigate the effects of HOTAIR in UVB-induced apoptosis and inflammatory injury in human keratinocytes (HaCaT cells). Quantitative real-time polymerase chain reaction was performed to analyze the expression levels of HOTAIR, PKR, TNF-α, and IL-6. Cell viability was measured using trypan blue exclusion method and cell apoptosis using flow cytometry and western blot. ELISA was used to measure the concentrations of TNF-α and IL-6. Western blot was used to measure the expression of PKR, apoptosis-related proteins, and PI3K/AKT and NF-κB pathway proteins. UVB induced HaCaT cell injury by inhibiting cell viability and promoting cell apoptosis and expressions of IL-6 and TNF-α. UVB also promoted the expression of HOTAIR. HOTAIR suppression increased cell viability and decreased apoptosis and expression of inflammatory factors in UVB-treated cells. HOTAIR also promoted the expression of PKR. Overexpression of HOTAIR decreased cell viability and increased cell apoptosis and expression of inflammatory factors in UVB-treated cells by upregulating PKR. Overexpression of PKR decreased cell viability and promoted cell apoptosis in UVB-treated cells. Overexpression of PKR activated PI3K/AKT and NF-κB pathways. Our findings identified an essential role of HOTAIR in promoting UVB-induced apoptosis and inflammatory injury by up-regulating PKR in keratinocytes.